Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 28400 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is Reithrodontomys megalotis (Baird, 1857)" ] } The dataset includes 28400 records from 90 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0003538-150410134957023/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences